Avaliação do mercado de ativos florestais destinados à compensação ambiental no estado de São Paulo, SP. - Borghi, Tatiana Cintra (Universidade Federal de São Carlos, 2020)
Environmental offset is a public policy instrument used for the environmental management of impact mitigation in the Brazilian territory, based on the polluter-pays principle, thus any activities or ventures that use natural resources and that are considered effective or potentially polluting or capable of causing environmental degradation, are required to compensate for such impacts. The main study object of this work is the rural property with native vegetation areas in excess of the legal preservation obligations, that is, the portion of native vegetation existing in the property that is free from any legal preservation obligation (compromised areas, legal reserve, permanent preservation areas). One of the aims of this work was to evaluate the environmental compensation market in the state of São Paulo, identifying the spatial distribution and biome of the available areas, quantifying the total area and prices applied, by watershed. Therefore, data collection was done directly with specialized companies and realtors, who commercialize these areas that make up the environmental compensation market. Pricing was found in Reais (R$) per area measure (hectares or square meters) and varies according to the watershed, the biome, the amount and the availability of the area. Another goal was to present a case study of a property located in the municipality of Salto de Pirapora (SP), which is used only for environmental compensation of environmental licenses, through environmental easement. The data were obtained directly from the property owner company, regarding the way the property was made available to the market and the values applied to the negotiations. In this case, it was found that the prices are higher compared to the values obtained for the state of São Paulo, as they add other issues such as environmental studies, records in real estate notices, responsibility for preservation, time of analysis of the environmental agency. It is concluded that prices vary mainly according to the purpose of the compensation. Larger areas are intended for offsetting legal reserves from other rural properties and tend to have a low price by area measure, compared to smaller areas that are generally intended to offset environmental permits (vegetation cutting, intervention in permanent preservation areas, etc.). This business model can encourage rural producers to value their areas with vegetation, thus resulting in the conservation of the forests in these properties.
Evaluation of the forest assets market for environmental offset in the state of São Paulo, SP.
Keywords: Economia ambiental; Imóvel rural; Legislação ambiental; Servidão ambiental; Licenciamento ambiental; Environmental Economics; Rural property; Environmental legislation; Environmental easement; Environmental Licensing; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS